In silico Pharmacokinetics and Molecular Docking of Selected Compounds against Target Proteins of Alzheimer’s Disease - Jaswitha, Tirumalasetti (International Journal of Pharmaceutical & Biological Archive, 2021)
Alzheimer’s disease (AD) is a multifactorial disease, which can be simply stated as a progressive and irreversible chronic disease of aging. The main purpose of the existing work was to find out the anti-Alzheimer’s activity of repurposing drugs and novel chemical compounds. In the present in silico study, IQ3, echothiophate, 15d-PGJ2, mefenamic acid, phentolamine, and nateglinide were screened on four major protein targets AChE, beta-secretase 1, C-Jun N-terminal kinase-3, and peroxisome proliferator-activated receptor γ by molecular docking using Autodock Vina software. The ligands are then compared to the well-known standard inhibitors of their specific proteins. Using pkCSM and SwissADME software, pharmacokinetic properties were also analyzed. In accordance with the molecular docking scores, out of the screened ligands IQ3, nateglinide, phentolamine, and mefenamic acid significantly linked with chosen targets of AD. In the present study, no drug violates Lipinski’s fifth rule. All the ligands have blood–brain barrier permeability and intestinal absorption. Toxicity prediction results showed that all ligands are non-hepatotoxic with the exception of ligand IQ3, and no AMES toxicity was observed with the exception of IQ3, phentolamine. The current study suggested that among the six ligands evaluated, nateglinide and mefenamic acid may be effective in improving memory in AD and dementia on the basis of molecular docking and pharmacokinetic parameters.